Multistep Continuous‐Flow Synthesis in Medicinal Chemistry: Discovery and Preliminary Structure–Activity Relationships of CCR8 Ligands. Issue 28 (28th May 2013) - Petersen, Trine P.; Mirsharghi, Sahar; Rummel, Pia C.; Thiele, Stefanie; Rosenkilde, Mette M.; Ritzén, Andreas; Ulven, Trond
Abstract: A three‐step continuous‐flow synthesis system and its application to the assembly of a new series of chemokine receptor ligands directly from commercial building blocks is reported. No scavenger columns or solvent switches are necessary to recover the desired test compounds, which were obtained in overall yields of 49–94 %. The system is modular and flexible, and the individual steps of the sequence can be interchanged with similar outcome, extending the scope of the chemistry. Biological evaluation confirmed activity on the chemokine CCR8 receptor and provided initial structure–activity‐relationship (SAR) information for this new ligand series, with the most potent member displaying full agonist activity with single‐digit nanomolar potency. To the best of our knowledge, this represents the first published example of efficient use of multistep flow synthesis combined with biological testing and SAR studies in medicinal chemistry. Abstract : Multistep flow synthesis : Efficient assembly of chemokine receptor ligands in a three‐step continuous‐flow synthesis system is reported. The system combines three diverse building blocks in high yields and allows modifications in any part of the scaffold (see scheme; BPR=back‐pressure regulator). The compounds represent a new series of CCR8 ligands, with the most potent member displaying full agonist activity and single‐digit nanomolar potency.